Pengaruh Persepsi Harga, Kualitas Produk, Citra Merek, dan Layanan Purna Jual Terhadap Keputusan Pembelian dan Dampaknya Terhadap Kepuasan Pelanggan Smartphone Asus. Studi Kasus di PT. Datascrip - Cahya, Nur; Shihab, Muchsin Saggaff (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This study aims to analyze the effect of perceive price, product quality, brand image and after sales service on purchase decision and the implications on customer satisfaction of Asus smartphone. This research is descriptive-quantitative in nature. Secondary data was obtained through various journals, books and related information. Primary data were obtained using questionnaire distributed to Asus customers in Datascrip service center. Using incidental sampling technique, a total sample of 245 Asus customers were obtained. Path analysis was employeds. Various statistical tests such as validity, reliability, normality tests were employed. The results showed that the variables’ of perceive price, product quality, brand image and after sales service partially and simultaneously had a significant and positive effect on purchase decision. Furthermore, only the variables of after sales service were found to have a direct effect on customer satisfaction. Purchase decision has a significant effect on customer satisfaction. In order to increase purchasing decision, it is recommended that Asus to pay attention to brand image by creating products that have attractive physical identities, in terms of packaging, color and design, and to create customer satisfaction should pay attention to facilities and infrastructure of service center as much as possible.